Human Endothelial Cells Modulate CD4+ T Cell Populations and Enhance Regulatory T Cell Suppressive Capacity - Lim, Wen Chean; Olding, Michael; Healy, Eugene; Millar, Timothy M. (Frontiers in Immunology, 2018)
Endothelial cells (ECs) line the luminal surface of blood vessels and have an active role in the recruitment of leukocytes, including immune cell activation. Regulatory T cells (Tregs) are immune suppressor cells that maintain peripheral tolerance and must interact with the endothelium as they traffic into tissue. We hypothesised that human ECs could modulate Tregs and their suppressor function. Co-cultures of CD4+ T cells with human umbilical vein ECs (HUVECs) or dermal microvascular ECs (HDMECs) were conducted and analysed for activation and proliferation after 72 and 120 hours using flow cytometry. In monocyte-depleted cultures, human ECs were found to support CD4+ T cell proliferation in the presence of external mitogens phytohaemagglutinin (PHA) or anti-CD3/28 antibodies (aCD3/28). Activation was shown by CD25 expression in these cells that also transiently expressed the Treg transcription factor FOXP3. HUVECs supported the specific concurrent proliferation of both effector T cells and Tregs when co-cultured with aCD3/28. Purified Tregs were also functionally activated by prior co-culture with EC to suppress effector T (Teff) cell proliferation. Both direct co-culture and indirect co-culture of EC and Treg showed activation of the Treg suppressive phenotype. However, whereas HUVEC showed enhancement of suppression by both mechanisms, HDMEC only supported Treg suppressive activity via the contact-independent mechanism. In the contact-independent cultures the soluble mediators IL-6, GM-CSF or G-CSF released from endothelial cells following interferon (IFN)-γ activation were not responsible for the enhanced Treg suppressor function. Following direct co-culture, Treg expression of inhibitory receptors PD-1 and OX40 was elevated while activated EC expressed the counter ligands PD-L1 and PD-L2. Therefore, human ECs have a role in supporting T cell proliferation and increasing Treg suppressor function. This ability of EC to enhance Treg function could offer novel targets to boost Treg activity during inflammatory disorders.